International perspectives on corporate finance : the Lintner model and dividend policy among publicly listed firms in Barbados - Robinson, C. Justin (2005)
Extends the literature on corporate dividend policy in emerging markets by investigating the appicability of the Lintner model to the dividend policy of publicly listed firms in Barbados.